Enhancing Student Reading Skill through Strategy of Directed Reading Thinking Activity (DRTA) - Umiyati jabri; Nurmi Nadhira (Universitas Muhammadiyah Enrekang, 2020)
This research examines the effect of the DRTA strategy as an effort in enhancing the students' reading comprehension skills in class V SD 41 Enrekang. A research methodology is a quantitative method for classroom action research. This review focuses on student learning outcomes and processes. The study was conducted at Enrekang 41 Elementary School, Enrekang, with the subject of the fifth-grade students of Enrekang 41 Elementary School, Enrekang, consists of 21 students. The CAR is carried out in four stages: planning, implementing actions, observing, and reflecting. From the implementation obtained data collected by learning outcomes tests. Then the data is analyzed and processed quantitatively. The results of the study showed that Directed Reading Thinking Activity (DRTA) in the first cycle is in the less category (K), and after the second cycle action is carried out, there is an improvement in students’ scores and has reached the specified indicators. From the result, the researcher concludes that the students' reading comprehension skills in Indonesian subjects in class V SD 41 Enrekang, Enrekang Regency has an improvement after applying of the strategy of Directed Reading Thinking Activity (DRTA).